THE USE OF DIFFERENT LINGUISTIC REGISTERS IN VARIOUS SOCIAL SETTINGS IN ENGLISH AND UZBEK LANGUAGES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
One of the main features of a language is the way it varies according to the social context in which it is used. This phenomenon is known as 'linguistic register' — the variation in language use depending on the setting, audience, and purpose of communication. In other words, language register can be defined as how a speaker uses language differently in different circumstances. Both in English and Uzbek languages, the use of linguistic registers plays a significant role in shaping communication across different social settings. This article examines how different registers are used in English and Uzbek across formal, informal, and neutral contexts, and highlights the cultural and social factors that influence these variations.